Evaluation of the effect of the concentration of seeding particles on spike-excitation doppler UVP measurement - Thang, Nguyen Tat (Vietnam Journal of Mechanics, 2021)
In the study of fluid flows, one of the important parameters is the spatial-temporal velocity distribution. Experimental measurement of the parameter is required for the development and validation of various models in this field. Techniques for the measurement of flow velocity at single points have been in operation with great success for many years. However, there are situations where the measured data at one point is obviously not enough to understand structures in, e.g., turbulent/transient flows. One of the well-established and powerful methods for measuring velocity distribution is the UVP - Ultrasonic Velocity Profile method that enables measurements of the instantaneous velocity profile along a measurement line, i.e. the sound path. The new application of spike excitation along with the Doppler signal processing to the UVP method has recently been successfully tested. Regarding this new method, factors influencing the measurement result require further careful investigations. This study addresses, to some extent, the effect of the seeding-particle concentration on the results of spike-excitation UVP measurements. For the investigation, experimental measurements of water pipe flow have been carefully executed for a wide range of the particle concentration. The dependence of the measured data on the particle concentration is evaluated and reported. The result of this study suggests an appropriate range of the seeding-particle concentration in setting up spike-excitation UVP measurements.